Study of knowledge, behaviour and practice of biomedical waste among health personnel - Chowdhary, Anjuman (International Journal Of Community Medicine And Public Health, 2018)
Background: Healthcare wastes are of great importance due to its hazardous nature. As World Health Organization (WHO) indicated, some of healthcare wastes are considered the most hazardous and potentially dangerous to human health and pollute the environment. With this background this study was undertaken to assess awareness, behavior and practices healthcare personnel about biomedical waste, its hazards and management. Methods: This one cross-sectional study was conducted at S.V.B.P. hospital associated with L.L.R.M. medical college, Meerut. A total of 291 healthcare personnel who consented for interview were interviewed biomedical waste management rules and observed for biomedical waste management practices by using redesigned and a pretested questionnaire. The data was analysed by using SPSS software. Results: Awareness regarding bio-medical waste management rules was 67% in doctors, 60% in nurses, 57% among lab technicians, but the sanitary staff was not aware about this. Awareness about category of BMW, number, colour coding, disposed content, labelling and cover of waste containers and segregation of waste were more among nurses and lab technicians in comparison to doctors but minimum among sanitary staff. All the respondents (100%) doctors, nurses and lab technicians knew that HIV and Hepatitis B transmitted through Bio medical waste but their awareness regarding Hepatitis C and other diseases was very low. 74% of sanitary Staff did not know that these diseases could be transmitted through bio medical waste. Conclusions: Healthcare facilities should get their healthcare personnel trained from accredited training centers.